The World Food Assembly Manifesto - Assembly, World Food (Kasarinlan: Philippine Journal of Third World Studies, 2007)
Developing country governments need to adopt national policies of food autonomy, in full consultation with peasant associations and other groups representing the urban and rural poor. These policies must provide for a reorientation of farm finance, prices and other incentives to revitalize rural communities and encourage domestic foodcrop production. Meanwhile, governments in the North must evolve new agricultural strategies geared to their people's real nutritional needs, a healthy rural economy keeping small and family farmers on the land, and sustainable farm practices to protect the environment.